Role of Intravenous Levetiracetam in Seizure Prophylaxis of Severe Traumatic Brain Injury Patients - KIRMANI, BATOOL F.; Mungall, Diana; Ling, Geoffrey (Frontiers in Neurology, 2013)
Traumatic brain injury (TBI) can cause seizures and the development of epilepsy. The incidence of seizures varies from 21% in patients with severe brain injuries to 50% in patients with war-related penetrating TBI. In the acute and sub-acute periods following injury, seizures can lead to increased intracranial pressure and cerebral edema, further complicating TBI management. Anticonvulsants can be used for seizure prophylaxis according to the current Parameters of Practice and Guidelines in a subset of severe TBI patients, and for a limited time window. Phenytoin is the most widely prescribed anticonvulsant in these patients. Intravenous levetiracetam, made available in 2006, is now being considered as a viable option in acute care settings if phenytoin is unavailable or not feasible due to side-effects. We discuss current data regarding the role of intravenous levetiracetam in seizure prophylaxis of severe TBI patients and the need for future studies.